Responsibility of BUMN through Goods Loading and Unloading Agreements to the Risk of Damage - marif, marif; Nurhaedah, Nurhaedah (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This research aims to find out and analyse the legal responsibility of state-owned companies for damage to goods in loading and unloading agreements and factors that cause damage to goods in the implementation of loading and unloading agreements in state-owned companies. This research uses empirical research methods or field research, namely research whose sources come from data in the field. The location of the research was carried out at one of the BUMNs, namely PT Pelindo Terminal Petikemas New Makassar. Types and sources of legal research data include primary and secondary data. Data collection techniques with interviews, observation and literature study. The results of this study indicate that PT Pelindo Terminal Petikemas New Makassar is responsible for damage or loss of goods that occur during the process of implementing loading and unloading activities (stevedoring, cargodoring, and receiving/delivery). And is not responsible for losses arising outside the implementation of loading and unloading activities carried out. Regarding the factors of damage to goods at PT Pelabuhan Indonesia IV (Persero) Regional 4 Makassar include: Weather factors, equipment factors, human error factors, carrier delay factors, and goods condition factors.The recommendation of this research is that PT Pelindo Terminal Petikemas New Makassar should make a written transportation agreement to avoid the blurring of the agreement if in the future there is a dispute regarding the agreement, and PT Pelindo Terminal Petikemas New Makassar Makassar should pay more attention to what causes damage to the goods by more actively conducting internal meetings and adding loading and unloading equipment as well as intensive coaching and training of its workforce so as to reduce damage to goods so that the company does not suffer losses.